Strategi Manajemen Bisnis Pasca Pandemi Covid-19 - Ika Fitriyani; Nining Sudiyarti; M. Nur Fietroh (Indonesian Journal of Social Sciences and Humanities, 2020)
Micro, Small and Medium Enterprises, the trade sector is currently faced with the problem of declining sales, difficulty in obtaining raw materials, impeded production and distribution, capital difficulties, lack of information technology knowledge and business network constraints. This study aims to determine the business management strategies of SMEs in Sumbawa Regency after the Covid-19 pandemic by referring to questions raised by Pedersen and Ritter (2020), namely: position, plan, perspective, project, and prepare. This type of research is descriptive, data collection methods using structured and gradual interviews. The number of respondents was 27 people. The data analysis technique uses descriptive qualitative. The results of the study explained that the post-Covid-19 business management strategy for MSME entrepreneurs can provide improvement and development of good business sustainability by implementing management strengthening in the fields of marketing, human resources, finance and operations as strategic steps to create an efficient and effective business existence. The conclusion of this study is that SMEs are required to have good knowledge management and absorptive capacity to improve business performance. Furthermore, for future research, it is expected to study more sources and references, namely by adding variables and deeper analysis to obtain more complete research results by using a mixture of quantitative and qualitative methods.